Autism as a challenge in the medical, diagnostic and therapeutic dimension - Jach-Salamon, Natalia (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Autism is a holistic, extensive development disorder. It influences the course of various processes and significantly reduces the possibility of an independent life, independent of other people's care, for those affected by it. According to modern knowledge, autism is classified as a neurobiological problem. It arouses great interest among researchers, while still being relatively poorly understood [24]. The aim of the study was to review knowledge in the area of ​​the multifaceted basis of autism and the diagnostic and therapeutic nature of autistic disorders. Description of the state of knowledge: Currently, autism is treated as a neurodevelopmental disorder, the symptoms of which usually appear before the child reaches the age of three. People affected by this disorder exhibit deficits in social interactions, verbal and non-verbal communication, as well as display disturbed (limited or stereotypical) behavior patterns. Autism as a heterogeneous disease may also coexist with various types of disorders, including mental retardation, epilepsy, anxiety or mood disorders [1, 35]. Summary: The prognosis for development, adaptation and recovery from autism is not optimistic. Despite advances in diagnosis, therapy, and education, success to a full cure is still "rare". On the other hand, it is important that the situation of people affected by these development disorders is gradually improving, thanks to better and better educational and therapeutic programs, as well as thanks to the initiatives taken to increase the opportunities for these people to participate in social life.